80 questions... 24 divided by .3
First simplify <span>t^2-t-12, which becomes (t-4)(t+3)
now you can rewrite the expression as one term; (t-4)(t+3)(t+1)/(t+1)(t+3)
cancel out (t+3) and (t+1) which leaves the answer as (t-4)</span>
Answer: a) 24 b) infini
Step-by-step explanation: a) parce que tu peut faire que 24 somme pour faire 23. B) infini car tout plus haut 100 fonctione
Answer:
9
Step-by-step explanation:
-4(6x+3)= -12(x+10)
<u><em>Let's do the first part:</em></u>
-4(6x+3)
<em>**distribute**</em>
-4 x 6x = -24x; -4 x 3 = -12 ->>> -24x - 12
<u><em>Let's do the second part:</em></u>
-12(x+10)
<em>**distribute**</em>
-12 x x = -12x; -12 x 10 = -120 ->>> -12x -120
-24x -12 = -12x - 120
<em>**Move variable to the left-hand side and change its sign**</em>
-24x +12x -12 = -120
-12x - 12 = -120
-12x = 108
x = 108/-12
x=9
Hi the answer to your question is
((3y - 3.5) / (3y + 6)) * 25.5 = (17
/ 25.5) * 25.5
((3y - 3.5) / (3y + 6)) * 25.5 = 17
(76.5y - 89.25) / (3y + 6) = 17
((76.5y - 89.25) / (3y + 6)) * (3y +
6) = 17 * (3y + 6) 76.5y - 89.25 = 51y + 102 76.5y - 51y = 102 + 89.25
25.5y = 191.25
y = 191.25 / 25.5
<span>y = 7.5</span>